Exploring the Impact of Independent Commissioners, Institutional Ownership, Profitability, and Leverage on Tax Avoidance - Sri Ayem; Virdawati Virdawati (International Journal of Economics Development Research (IJEDR), 2024)
This study investigates the impact of an autonomous board of commissioners, institutional ownership, profitability, and leverage on tax avoidance. The sample utilized in this study consists of manufacturing companies listed on the Indonesian Stock Exchange (BEI) throughout 2018-2022. The data collection employed a purposive sampling technique, resulting in a sample of 40 companies to analyze 181 annual financial reports. This research technique employs multiple regression analysis. The research findings indicate that the independent board of commissioners has little impact on tax avoidance. Institutional ownership and leverage exert a detrimental effect on tax avoidance. Profitability has a favorable impact on tax avoidance.